Enhancing problem-solving and critical thinking through contextual learning and TAI integration - Farisman Ziliwu; Ali Mahmudi (Inovasi Kurikulum, 2025)
Problem solving and critical thinking are essential skills in 21st-century mathematics education. The Team Assisted Individualization (TAI) model promotes both collaborative learning and individual responsibility, while contextual teaching links mathematical concepts to real life, making learning more meaningful. However, combining these two approaches has received limited attention, particularly in enhancing students’ problem-solving and critical thinking skills. This study aims to examine the enhancement of these skills through the implementation of the TAI model integrated with a contextual learning approach. A pre-experimental method with a one-group pretest-posttest design was employed. Participants were Grade XI students at a senior high school in Yogyakarta, focusing on the topic of algebraic derivatives. Data were collected using a test designed to assess problem-solving and critical thinking skills, before and after the intervention. Paired sample t-tests were used to analyze the score differences. The findings revealed a significant improvement in students’ problem-solving and critical thinking skills following the intervention. This suggests that combining TAI and contextual learning is effective in fostering mathematical thinking competencies. Further research is recommended to explore the roles of group collaboration and individual learning in supporting the development of key 21st-century skills.   Abstrak Kemampuan pemecahan masalah dan berpikir kritis merupakan keterampilan esensial dalam pembelajaran matematika abad ke 21. Model Team Assisted Individualization (TAI) diketahui dapat mendorong kolaborasi dalam kelompok sekaligus mendukung pembelajaran individu, sedangkan pendekatan kontekstual mengaitkan materi dengan situasi nyata untuk meningkatkan relevansi dan makna pembelajaran. Namun, integrasi keduanya masih jarang dikaji secara mendalam, khususnya dalam konteks pengembangan kemampuan pemecahan masalah dan berpikir kritis. Penelitian ini bertujuan untuk mengetahui peningkatan kedua kemampuan tersebut melalui penerapan model TAI yang terintegrasi dengan pendekatan pembelajaran kontekstual. Metode yang digunakan adalah pra eksperimen dengan desain satu kelompok pretest posttest. Subjek penelitian adalah siswa kelas XI di salah satu SMA di Yogyakarta dengan topik turunan fungsi aljabar. Instrumen yang digunakan berupa tes pemecahan masalah dan berpikir kritis yang diberikan sebelum dan sesudah perlakuan. Analisis data dilakukan dengan uji t berpasangan untuk mengetahui signifikansi perbedaan skor pretest dan posttest. Hasil menunjukkan peningkatan yang signifikan dalam kemampuan pemecahan masalah dan berpikir kritis siswa. Penelitian lanjutan disarankan untuk mengevaluasi kontribusi kerja sama kelompok dan peran individu dalam mendukung pencapaian keterampilan abad ke 21 secara lebih mendalam. Kata Kunci: kemampuan berpikir kritis; kemampuan pemecahan masalah; model pembelajaran kooperatif; pendekatan pembelajaran kontekstual; team-assisted individualization